New Perspectives on Aspect and Modality in Chinese Historical Linguistics - Meisterernst, Barbara; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents new perspectives on the study of Aspect and Modality in Chinese Historical Linguistics. Based on the international Workshop on Aspect and Modality in Chinese, the book includes the latest research findings in the field to make them available not only to specialists in Classical and Buddhist Chinese, but also to researchers and students of general linguistics and of the universals of language. It also discusses different aspects of the AM (Aspect-Modality) and the TAM (Tense-Aspect-Modality) system of Chinese. It provides a comprehensive overview of both of the universally related systems of aspect and modality. The first part of the book focuses on aspectual features of Chinese; these include basic studies on the syntactic representation of the aspectual structure of the verb phrase in Archaic Chinese, the aspectual function of different object constructions and their development, temporal features of the verb phrase, and the aspectual functions of nominalization processes. The second part includes articles highlighting different aspects of the modal system or the interplay between tense, aspect and modality in Chinese, including a survey on the history of studies on modality in Chinese and the modal and temporal aspectual/markers indicating future meanings, a specialized study on modal deontic verbs in the Buddhist Vinaya texts, the modal function of rhetorical questions in Buddhist Chinese, and a study on the diachronic development of the aspectual and modal system in Chinese.
The Syntax of the Verbs in Archaic Chinese YU Construction -- The Development of the Adverb "QIE 且" in Middle Chinese -- New Insights on the Historical Evolution of the Differential Object Marking in Chinese -- Preliminary Investigation of the Temporal Features of Classical Chinese Verbs -- The History of the Instrumental Nominalization in Chinese -- Some Reflections on the Use and Distribution of Interrogative Pronouns in Medieval Chinese Texts -- Future Meanings, Selection and Volition -- The Diachronic Development of the Aspectual and Modal System of Chinese -- Modality in the General Linguistic Investigations Carried out in China before 1949 -- The Modal Verb 應 in Buddhist Vinayas.
Keywords: Asia -- Languages; Historical linguistics; Oriental languages; Asian Languages; Historical Linguistics; Oriental or Semitic Languages